2008
DOI: 10.1099/jmm.0.47527-0
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral immunization of mice with a genetically inactivated pertussis toxin DNA vaccine induces cell-mediated immunity and protection

Abstract: The immunogenicity and protective efficacy of a DNA vaccine encoding a genetically inactivated S1 domain of pertussis toxin was evaluated using a murine respiratory challenge model of Bordetella pertussis infection. It was found that mice immunized via the intramuscular route elicited a purely cell-mediated immune response to the DNA vaccine, with high levels of gamma interferon (IFN-c) and interleukin (IL)-2 detected in the S1-stimulated splenocyte supernatants and no serum IgG. Despite the lack of an antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
9
1
Order By: Relevance
“…130 Li et al 131 reported that a recombinant pertussis DNA vaccine expressing the pertussis toxin subunit 1 (PTS1), filamentous hemagglutinin (FHA) gene and pertactin (PRN) in pVAX1 were reported to elicit both antibody and cell-mediated immune responses in NIH strain of mice upon delivery by a parenteral route. This was in contrast to our studies 132 in which a genetically-inactivated pertussis toxin pcDNA3.1-based DNA vaccine administered by the intramuscular route was found to generate a purely cell-mediated immune response. We have further found that boosting DNA vaccine-primed mice with pertussis toxoid yielded excellent antibody as well as cell-mediated immune responses (Fry S, Chen, Daggard and Mukkur T, unpublished).…”
Section: Potential Mechanisms Underpinning Immunity To Infection Withcontrasting
confidence: 54%
“…130 Li et al 131 reported that a recombinant pertussis DNA vaccine expressing the pertussis toxin subunit 1 (PTS1), filamentous hemagglutinin (FHA) gene and pertactin (PRN) in pVAX1 were reported to elicit both antibody and cell-mediated immune responses in NIH strain of mice upon delivery by a parenteral route. This was in contrast to our studies 132 in which a genetically-inactivated pertussis toxin pcDNA3.1-based DNA vaccine administered by the intramuscular route was found to generate a purely cell-mediated immune response. We have further found that boosting DNA vaccine-primed mice with pertussis toxoid yielded excellent antibody as well as cell-mediated immune responses (Fry S, Chen, Daggard and Mukkur T, unpublished).…”
Section: Potential Mechanisms Underpinning Immunity To Infection Withcontrasting
confidence: 54%
“…Methods used for the stimulation of splenocytes cultured in vitro and collection of splenocyte supernatants were as described elsewhere (Fry et al 2008). Estimation of IFN-γ, as an indirect indicator of cell mediated immunity (CMI) was carried out for vaccinated and control groups of mice following stimulation with planktonic or biofilm S. aureus respectively.…”
Section: Estimation Of Interferon Gamma (Ifn-γ) In Antigen Stimulatedmentioning
confidence: 99%
“…Anti-S. aureus specific antibody isotypes, IgG, IgG 1 and IgG 2a, of pre-challenge serum samples of mice immunized with either planktonic or biofilm vaccine were determined following the indirect ELISA procedure as described elsewhere (Fry et al 2008). Formalin-killed S. aureus 51 suspended in PBS representing planktonic or biofilm cells was used to coat the wells in the Nunc-Immuno ™ MicroWell ™ 96 plates (Castle Hill, NSW, Australia).…”
Section: Detection Of Antigen-specific Antibody Isotypes In Serum Sammentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative approaches based on the use of live-attenuated strains expressing PT-9K/129G [82], of the whole cell vaccine made from Bordetella strain overexpressing PT-9K/129G [83], of outer membrane vesicles derived from the wild-type strain [84], of genetically detoxified S1 delivered as DNA vaccine [85,86] or expressed by BCG [87], although very promising and probably effective in inducing a Th1 immune response, are still at the experimental stage. On the other hand, evidence that the vaccine containing the genetically detoxified PT-9K/129G induced an earlier and longer-lasting protection from disease at lower doses compared with chemically inactivated PT suggests that the superior immunogenicity and protective efficacy is due to better quality of the immune response.…”
Section: Expert Commentarymentioning
confidence: 99%